Rituais e folkcomunicação : um sistema de comunicação simbólico no São João do Maranhão - Almeida, Francinete Louseiro de (2018)
To elaborate this work, we set up the “arraial” and analyze the rituality of the “São João” Feast that belongs to the state of Maranhão as a system of symbolic communication, which expresses and communicates the identity of a people. In the heating of the bonfires, we have located, through ethnographic research, the object of study, the “São João” Feast, adopting, as a methodology of research, the philosophical hermeneutics of Gadamer, making use of the concept of hermeneutical circle, divided into three parts, for reading, that correspond to the three aspects of rituals that have been analyzed: the comonthlys, the apparel and the spatiality. On the stage of the party we emphasize the concepts of myth, rite and rituals. We define the ritual as this symbolic communication system where agents and social subjects develop social relations and consolidate their experience in society. We present the parties and events as places for building identities and we locate the party researched in its symbolic fields. We have also explored, the concepts of folklore and culture, which give support for this research. In the folklore tent we use the theory of “Folkcomunicação”, because we analyze a festival of popular culture, via communication. We also share the concept of culture approached in this theory, from which we appropriate, to substantiate the research. In the guarnicê of the ritual, we present the interpretation/analysis of the research considering that, as we are working with the philosophical hermeneutics of Gadamer, we considered the party from the Hermeneutical Circle, presenting first the party pre understanding, the three parties in which the party was divided into for reading and finally its interpretation.